Dynamic signal processing by ribozyme-mediated RNA circuits to control gene expression. Issue 10 (27th April 2015) - Shen, Shensi; Rodrigo, Guillermo; Prakash, Satya; Majer, Eszter; Landrain, Thomas E.; Kirov, Boris; Daròs, José-Antonio; Jaramillo, Alfonso
Abstract: Organisms have different circuitries that allow converting signal molecule levels to changes in gene expression. An important challenge in synthetic biology involves the de novo design of RNA modules enabling dynamic signal processing in live cells. This requires a scalable methodology for sensing, transmission, and actuation, which could be assembled into larger signaling networks. Here, we present a biochemical strategy to design RNA-mediated signal transduction cascades able to sense small molecules and small RNAs. We design switchable functional RNA domains by using strand-displacement techniques. We experimentally characterize the molecular mechanism underlying our synthetic RNA signaling cascades, show the ability to regulate gene expression with transduced RNA signals, and describe the signal processing response of our systems to periodic forcing in single live cells. The engineered systems integrate RNA–RNA interaction with available ribozyme and aptamer elements, providing new ways to engineer arbitrary complex gene circuits.